Case Report: Herpes Zoster in a Fully Vaccinated Child Without a History of Primary Varicella Infection - Sri Nauli Dewi Lubis; Nova Zairina Lubis (Indonesian Journal of Global Health Research, 2025)
Herpes zoster (HZ) is an acute skin infection caused by reactivation of the varicella-zoster virus (VZV), characterized by unilateral radicular pain and clustered vesicles following a dermatomal pattern. Although more commonly seen in older adults and immunocompromised individuals, HZ can also occur in immunocompetent children who have received complete varicella immunization, although this is rare. This report aims to describe a case of HZ in an immunocompetent child without a prior history of varicella infection and to raise clinical awareness of the possibility of HZ in low-risk pediatric populations. The method used is a case report with a descriptive clinical approach, including symptom evaluation, physical examination, and treatment with antiviral and supportive therapies. The findings indicate that HZ can be clinically diagnosed even in children considered low-risk. In conclusion, HZ should remain a differential diagnosis in children presenting with characteristic vesicular lesions, to ensure prompt recognition and appropriate management.